2018
DOI: 10.3390/ijms19072111
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization and Structure-Guided Mutational Analysis of the Transsulfuration Enzyme Cystathionine γ-Lyase from Toxoplasma gondii

Abstract: Sulfur-containing amino acids play essential roles in many organisms. The protozoan parasite Toxoplasma gondii includes the genes for cystathionine β-synthase and cystathionine γ-lyase (TgCGL), as well as for cysteine synthase, which are crucial enzymes of the transsulfuration and de novo pathways for cysteine biosynthesis, respectively. These enzymes are specifically expressed in the oocyst stage of T. gondii. However, their functionality has not been investigated. Herein, we expressed and characterized the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Despite the major importance of redox balance in survival of parasites and the role that cysteine production has in redox homeostasis, to date knowledge about the cysteine biosynthetic pathway in T. gondii is still very limited 27 . The protozoan parasite includes both the CBS and CGL enzymes of the reverse transsulfuration pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the major importance of redox balance in survival of parasites and the role that cysteine production has in redox homeostasis, to date knowledge about the cysteine biosynthetic pathway in T. gondii is still very limited 27 . The protozoan parasite includes both the CBS and CGL enzymes of the reverse transsulfuration pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The protozoan parasite includes both the CBS and CGL enzymes of the reverse transsulfuration pathway. We have shown previously that the putative CGL gene encodes a functional enzyme in T. gondii 27 . Herein, we establish that the parasite possesses an intact reverse transsulfuration pathway by cloning and characterization of the gene encoding putative CBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that both CBS and CGL from Toxoplasma gondii (TgCBS and TgCGL) are functional in toxoplasma (24), (40), implying that the reverse transsulfuration pathway is operative in the parasite. In particular, TgCBS can use both Ser and O-acetylserine (OAS) to produce Cth (24).…”
Section: Introductionmentioning
confidence: 99%